Synthesis of Organometallic Oligonucleotides through Oximation with Metalated Benzaldehydes - Maity S.K.; Lönnberg T.A. (AMER CHEMICAL SOC, 2022)
A phthaloyl-protected aminooxymethyl-C-2'-deoxyriboside building block has been prepared and incorporated in the middle of an oligodeoxyribonucleotide. Removal of the phthaloyl protection followed by on-support oximation with either mercurated or palladated benzaldehydes yielded oligonucleotides bearing the respective benzaldoxime metallacycles.